The incredible hulk - Arad, Avi; Hurd, Gale Anne; Feige, Kevin; Leterrier, Louis; Universal Pictures; Marvel Entertainment (California : Universal Pictures/Marvel Entertainment, 2008)
Scientist Bruce Banner has been living in the shadows, scouring the earth for an antidote. Warmongers dream of abusing his powers and won't leave Bruce alone. He suffers from his constant need to be with the only woman he has ever love, Betty Ross, and Bruce knows that he must return to civilization. The brilliant doctor is ruthlessly pursued by a nightmarish beast of pure adrenaline and aggression called The Abomination whose powers match that of the Hulk. Now, a fight of epic proportions ensues as Bruce must call upon the hero within to rescue New York City from total destruction
Title from title screen
Bonus disc: Feature commentary with director Louis Leterrier and Tim Roth; deleted scenes
Director of photography, Peter Menzies, Jr. ; editors, Rick Shaine, Vincent Tabaillon, John Wright ; music, Craig Armstrong ; costume designers, Renée Bravener, Denise Cronenberg ; production designer, Kirk M. Petruccelli
Cast: : Edward Norton, Liv Tyler, Tim Roth, William Hurt, Tim Blake Nelson, Ty Burrell
DVD Format
Woth optional English, Arabic, Danish, Dutch, Finnish, Hungarian, Icelandic, Norwegian, Swedish or Turkish subtitles
Keywords: Incredible Hulk (Fictitious character) -- Drama; Scientists -- Drama; Man-woman relationships -- Drama; Antidotes -- Drama; Superheroes -- Drama